Complex Limb Injuries: Limb Salvage Versus Amputation—A Mini Review and Meta-Analysis - Athanasios Serlis; Panagiotis Sgardelis; Themistoklis Vampertzis; Konstantinos Rizavas; Panagiotis Poulios; Georgios Konstantopoulos (Advances in Orthopedics)
Conclusion: Managing complex limb injuries effectively necessitates a comprehensive approach involving thorough assessment, multidisciplinary collaboration, and patient-centered care. Given the diverse factors influencing management and long-term outcomes, it is crucial to integrate medical expertise with patient preferences and expectations.